LAYERED MANTLE CONVECTION: A MODEL FOR GEOID AND TOPOGRAPHY - Lianxing W.; Anderson D.L. (My University, 1997)
The long-wavelength geoid and topography are dynamic effects of a convecting mantle. The long-wavelength geoid of the Earth is controlled by density variations in the mantle and has been explained by circulation models involving whole mantle flow. However, the relationship of long-wavelength topography to mantle circulation has been a puzzling problem in geodynamics. We show that the dynamic topography is mainly due to density variations in the upper mantle, even after the effects of lithospheric cooling and crustal thickness variation are taken into account. Layered mantle convection, with a shallow origin for surface dynamic topography, is consistent with the spectrum, small amplitude and pattern of the topography. Layered mantle convection, with a barrier about 250 km deeper than the 670 km phase boundary, provides a self-consistent geodynamic model for the amplitude and pattern of both the long-wavelength geoid and surface topography.
Keywords: GEOID; TOPOGRAPHY; MANTLE; CONVECTION